The energetic physiology of juvenile mussels, Mytilus chilensis (Hupe): The prevalent role of salinity under current and predicted pCO2 scenarios. (November 2018) - Duarte, C.; Navarro, J.M.; Quijón, P.A.; Loncon, D.; Torres, R.; Manríquez, P.H.; Lardies, M.A.; Vargas, C.A.; Lagos, N.A.
Abstract: As a result of human activities, climate forecasts predict changes in the oceans p CO2 and salinity levels with unknown impacts on marine organisms. As a consequence, an increasing number of studies have begun to address the individual influence of p CO2 and salinity but much remains to be done to understand their combined effects on the physiology and ecology of marine species. Our study addressed this knowledge gap by measuring the influence of current and predicted levels of p CO2 (380 and 1200 ppm, respectively) and salinity (20, 25 and 30 psμ) on the energetic physiology of juvenile mussels ( Mytilus chilensis ) from the south-eastern Pacific region. Our results indicate that a reduced salinity caused a significant reduction in clearance rate, absorption efficiency and scope for growth of this species. Meanwhile, an increase in p CO2 levels caused a reduction in excretion rates and interacted significantly with salinity in the rate of oxygen uptake measured in the mussel. These results suggest that potential changes in salinity might have a direct role on the physiology of M. chilensis . The effect of p CO2, although less prevalent among the variables measured here, did interact with salinity and is also likely to alter the physiology of this species. Given the ecological and economic importance of M. chilensis, we call for further studies exploring the influence of p CO2 across a wider range of salinities. Graphical abstract: Image 1 Highlights: Climate forecasts predict changes in p CO2 and salinity by the end of the century. Yet, their individual and combined effects on coastal species remain understudied. We assessed these effects on the physiology of juvenile mussels Mytilus chilensis . Salinity had a prevalent role over most mussel's physiology variables. pCO2 affected excretion rates and interacted with salinity on oxygen uptake. Abstract : A decline in salinity caused a reduction in clearance rates, absorption efficiency and scope of growth and an increase in excretion rates. Meanwhile, the projected rise in p CO2 reduced excretion rates and its interaction with a salinity decline resulted in higher oxygen uptake in an ecologically and economically important species.